Effectiveness of Law Enforcement of Banking Crimes in Banking Law in Indonesia - Windesi, Abalion Ayub; Renjaan, Henrikus; Siswani, Carina Budi (IHSA Institute, 2025)
This study examines the effectiveness of law enforcement against banking crimes within the framework of Indonesia’s Banking Law, particularly Law Number 10 of 1998. Although the legal framework normatively provides comprehensive provisions regarding bank secrecy, prudential principles, licensing, financial reporting, and sanctions, its implementation remains constrained by structural, technical, and institutional challenges. Using a normative juridical method supported by statutory, conceptual, and case approaches, this research analyzes the extent to which existing regulations have achieved the goals of legal certainty, justice, and utility as conceptualized in Radbruch’s theory. Findings indicate that overlapping institutional authority, limited investigative capacity, evidentiary barriers due to strict bank secrecy, and weak inter-agency coordination hinder effective enforcement. Additionally, disparities in digital forensic facilities and inadequate internal control systems within banking institutions reduce the ability to detect and prosecute violations. Through the lens of Soerjono Soekanto’s and Lawrence Friedman’s theories of legal effectiveness, this study concludes that while the normative substance is adequate, enforcement remains suboptimal. Strengthening institutional coordination, enhancing investigator competence, updating regulations to meet digital era banking complexities, and promoting a culture of transparency and compliance are essential for improving law enforcement outcomes